2019
DOI: 10.3390/jcm8081228
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Metabolically Healthy Obesity and the Risk of Cardiovascular Disease: A Systematic Review and Meta-Analysis

Abstract: Cardiovascular disease (CVD) risk in individuals with metabolically healthy obesity (MHO) is unclear. We searched databases from inception to May 2019. Data were pooled using a random effects model. Newcastle-Ottawa Scale assessment was performed. Primary and secondary outcomes were CVD risk and all-cause mortality. Forty-three studies involving 4,822,205 cases were included. The median percentage of females, age and duration of follow-up was 52%, 49.9 years and 10.6 years, respectively. The mean Newcastle-Ott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
45
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 49 publications
5
45
2
2
Order By: Relevance
“…Similar to a previous study [7], we found that MHO increased the risk of CVD and all-cause mortality compared with MHNW in the Asian population. This result was more striking for CVD than for all-cause mortality.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar to a previous study [7], we found that MHO increased the risk of CVD and all-cause mortality compared with MHNW in the Asian population. This result was more striking for CVD than for all-cause mortality.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, increased CVD risk is associated with lower BMI in Asians than in Caucasians [29]. Although a previous meta-analysis revealed sex and age to be significant effect modifiers [7], we found no significant effect, and further studies may be warranted. Sex-related differences in CVD risk could be explained by variations in visceral adipose tissue accumulation, deposition, and distribution which have been associated with insulin resistance and metabolic risks [30,31].…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…13 Previous meta-analyses on MHO primarily focused on the risk of cardiometabolic disease. [14][15][16][17] To date, no systematic review or metaanalysis reported the impact of MHO on the risk of cancer. One cohort study demonstrated that individuals with MHO were at increased risk of prostate cancer compared with individuals with metabolically healthy non-obesity (MHNO).…”
mentioning
confidence: 99%